The relationship between perceived stress, uncertainty emotions and hopelessness regarding pandemics in pregnant women - FIŞKIN, GAMZE (My University, 2022)
The objective of this study was to determine the emotional reactions of pregnant women towards the pandemic and to increase awareness of healthcare professionals on this subject. In this descriptive, cross-sectional, and correlational study, an online questionnaire was applied to 375 pregnant women (n = 375). Data were collected with pregnant information form, Intolerance of Uncertainty Scale and Beck Hopelessness Scale. The mean age of the pregnant women was 29.495 +/- 4.301, and the mean gestational week was 27.469 +/- 7.971. Pregnant women\"s levels of perceived stress and intolerance to uncertainty were high. There was a moderate positive correlation between stress and uncertainty levels of the women who stated that they experienced mild hopelessness. It is recommended to identify risky groups and provide the necessary psychological support by health professionals during the pandemic.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Sosyoloji; Social Sciences and Humanities; Psychology; Sociology; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); PSİKOLOJİ, MULTİDİSİPLİNER; Temel Bilimler (SCI); SOSYAL HİZMETLER; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); PSYCHOLOGY, MULTIDISCIPLINARY; PSYCHOLOGY; Natural Sciences (SCI); SOCIAL WORK; İş Sağlığı ve Terapisi; Güvenlik Araştırması; Sağlık (sosyal bilimler); Genel Sosyal Bilimler; Psikoloji (çeşitli); Genel Psikoloji; Halk, Çevre ve İş Sağlığı; Epidemiyoloji; Sağlık Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Occupational Therapy; Safety Research; Health (social science); General Social Sciences; Psychology (miscellaneous); General Psychology; Public Health, Environmental and Occupational Health; Epidemiology; Health Sciences; Social Sciences & Humanities; hopelessness; pandemic; perceived stress; pregnant women; uncertainty; INTOLERANCE; DEPRESSION; IMPACT